Dual-fluorescent reporter for live-cell imaging of the ER during DENV infection - Corliss, Lochlain; Holliday, Madeline; Lennemann, Nicholas J. (Frontiers in Cellular and Infection Microbiology, 2022)
Infection by flaviviruses leads to dramatic remodeling of the endoplasmic reticulum (ER). Viral replication occurs within virus-induced vesicular invaginations in the ER membrane. A hallmark of flavivirus infection is expansion of the ER membrane which can be observed at specific time points post infection. However, this process has not been effectively visualized in living cells throughout the course of infection at the single cell resolution. In this study, we developed a plasmid-based reporter system to monitor flavivirus infection and simultaneous virus-induced manipulation of single cells throughout the course of infection in real-time. This system requires viral protease cleavage to release an ER-anchored fluorescent protein infection reporter that is fused to a nuclear localization signal (NLS). This proteolytic cleavage allows for the translocation of the infection reporter signal to the nucleus while an ER-specific fluorescent marker remains localized in the lumen. Thus, the construct allows for the visualization of virus-dependent changes to the ER throughout the course of infection. In this study, we show that our reporter was efficiently cleaved upon the expression of multiple flavivirus proteases, including dengue virus (DENV), Zika virus (ZIKV), and yellow fever virus (YFV). We also found that the DENV protease-dependent cleavage of our ER-anchored reporter exhibited more stringent cleavage sequence specificity than what has previously been shown with biochemical assays. Using this system for long term time-lapse imaging of living cells infected with DENV, we observed nuclear translocation of the reporter signal beginning approximately 8 hours post-infection, which continued to increase throughout the time course. Interestingly, we found that increased reporter signal translocation correlated with increased ER signal intensity, suggesting a positive association between DENV infection and ER expansion in a time-dependent manner. Overall, this report demonstrates that the FlavER platform provides a useful tool for monitoring flavivirus infection and simultaneously observing virus-dependent changes to the host cell ER, allowing for study of the temporal nature of virus-host interactions.